Imaging cerebral microbleeds in Cushing's disease evaluated by quantitative susceptibility mapping: an observational cross-sectional study. Issue 4 (April 2021) - Jiang, Hong; Yang, Wenjie; Sun, Yuhao; Yan, Fuhua; Sun, Qingfang; Wei, Hongjiang; Bian, Liu-Guan
Abstract : Design: Cushing's disease (CD) is a rare clinical syndrome characterized by chronic exposure to hypercortisolism due to an adrenocorticotropic hormone-secreting pituitary adenoma. The adverse effects of chronic exposure to hypercortisolism on the human brain remain unclear. The purpose of this study was to assess the prevalence of cerebral microbleeds (CMBs) in CD patients and their associations with clinical characteristics. Methods: In this study, 48 active CD patients, 39 remitted CD patients, and 52 healthy control (HC) subjects underwent MRI. CD patients also underwent neuropsychological testing and clinical examinations. The number, locations, and volumes of CMBs were assessed on quantitative susceptibility mapping (QSM) images and with the Microbleed Anatomical Rating Scale. The correlation between CMBs and clinical characteristics was explored. Results: The prevalence of CMBs among active and remitted CD patients was higher than that among HCs (16.3%, 20.5%, and 3.3%, respectively). Moreover, the age of CD patients with CMBs were much younger than HCs with CMBs. Furthermore, the increased number of CMBs in active CD patients was associated with increased cerebrospinal fluid (CSF) volumes in remitted CD patients. Conclusions: Chronic exposure to hypercortisolism may be relevant to CMBs and significantly correlated with altered brain volumes in CD.